Effects Of Education Funding In Increasing Human Development Index - Yogiantoro, Mukhammad; Komariah, Diah; Irawan, Irawan (Universitas Negeri Semarang, 2019)
Every citizen has the right to get education with the aim of educating the nation's life as mandated in the opening of the 1945 Constitution. This study aims to determine the efficiency of education funding both from the APBN and the APBD purely in relation to increasing HDI and educational performance. The study uses influence analysis with multiple regression and descriptive quantitative research, with 3 variables, namely the large variable education funding from APBD and APBN, Education Performance and Human Development Index. The sample selection method used was purposive sampling, namely in Regencys / Cities in Central Kalimantan in the Period of 2015 - 2017. Research resulted in a relationship between education funding and HDI, Education and Performance Funds for Education and HDI and Educational Performance. Educational performance in this case is measured by teacher qualifications, teacher certification, educational ratios (Teachers: Students and Classes: Students), facilities and infrastructures physical condition, Gross Participation Rate (APK), Pure Participation Rate (APM), and Dropout Numbers. In the multiple regression, the effect of education funding both from the APBD and the APBN does not affect more dominantly in increasing Human Development Index.